Toxicity of cadmium salts on indicators of embryogenesis of rats - Kolosova, I. I.; Shatorna, V. F. (Regulatory Mechanisms in Biosystems, 2022)
Cadmium is a toxic heavy metal which is considered a dangerous environmental pollutant and has a detrimental effect on the organs of the reproductive system, the period of implantation and the development of embryos. The experiment presented in this article established the effect of cadmium salts (chloride and citrate) on the general progress of embryogenesis. For this purpose, 60 rats were randomly divided into three groups: control, experimental group with cadmium chloride exposure and experimental group with cadmium citrate exposure. Cadmium chloride solvent, cadmium citrate solvent at a dose of 1.0 mg/kg and distilled intragastric water were injected from the first to the thirteenth (first subgroup) and from the first to the twentieth days of embryogenesis (second subgroup). When cadmium chloride was injected, total embryonic (by 4.24 and 3.67 times), pre-implantation (by 6.50 and 14.03 times) and post-implantation mortality (by 3.07 and 2.49 times) increased with a reduction of the number of surviving fetuses by 24.0% and 25.9% compared with the control group on the 13th and 20th days of embryogenesis respectively. At the same time, during exposure to cadmium citrate, indicators of total embryonic mortality increased by 4.02 and 3.52 times, pre-implantation mortality by 6.04 and 13.03 times, and post-implantation mortality by 3.09 and 2.26 times, and indicators of the number of live fetuses decreased by 18.3% and 22.2% in relation to the control group. When determining the accumulation of cadmium in embryos on the 20th day of gestation, polyelement analysis of biological materials using the atomic emission method with electric arc atomization revealed a 15.83-fold increase in cadmium chloride and 9.00 times in cadmium citrate relative to the control group. Embryolethality rates increased in animals of both experimental groups while the number of live fetuses per female decreased, which indicated an obvious embryotoxic effect of cadmium compounds. It is would be useful to conduct histological studies, which will help detect changes at the tissue level and possibly explain the level of embryonic mortality.